PDTM-34. TARGETING H3.3G34R/V RE-WIRING OF THE EPIGENOME IN PAEDIATRIC GLIOBLASTOMA OF CHILDREN AND YOUNG ADULTS. (5th November 2018) - Bjerke, Lynn; Mackay, Alan; Carvalho, Diana; Pemberton, Helen; Molinari, Valeria; Vinci, Maria; Carceller, Fernando; Marshall, Lynley; Moore, Andrew; Montero Carcaboso, Angel; Lord, Chris; Hargrave, Darren; et al.
Abstract: Around 15% of cerebral hemispheric glioblastomas (GBM) of children and young adults harbour G34R/V mutations in H3F3A, encoding the histone H3.3 variant. These tumours have a peak incidence in late adolescence but are found up to 30yrs of age, and have conflicting data as to their prognosis compared to histone wild-type cases. As little is known about its role in tumorigenesis, we sought to explore the underlying biology of H3.3G34R/V mutant GBM and identify novel avenues for therapeutic intervention through genomic, epigenomic and drug screening approaches in primary-patient-derived cultures. In combined retrospective and prospective cohorts of pHGG samples, H3.3G34R/V tumours formed a highly distinct methylation subgroup marked by global hypomethylation. They are enriched in several whole chromosomal arm DNA copy number losses, which at 4q appears to converge along with somatic mutation on the F-box protein family member FBXW7, known to play a role in MYCN stabilization. MYCN was previously identified to be differentially bound by H3K36me3, and we further identified a novel MYCN signature to be highly expressed in H3.3G34R/V tumours. Expression of the H3.3G34R/V mutation in pGBM cells leads to loss of H3K36me3 in cis, and differential genomic binding of the activating mark globally. This appears linked to distinct H3K36me3 enhancer profiles by ChIP-seq, with consistent targeting of lysine 36 demethylases KDM2A / KDM4A . Additional super-enhancers identified in H3G34R/V cells include NOTCH1 and SF3A2, with both Notch signalling and splicing factor gene expression signatures significantly upregulated in patient samples. Screening against a library of >400 chemotherapeutics and small molecules identified a specific dependency for H3.3G34R/V cells on several agents targeting AURKA (as previously linked to MYCN upregulation) but also multiple chemotypes of proteasome inhibitors and the survivin inhibitor YM155. These data identify new rationally-based therapeutic options for exploration in this subset of paediatric/young adult GBM.